(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
The study examined the conversational implicatures inherent in Buhari’s speeches using Gricean Cooperative Principles. The study used qualitative research method to account for, interpret and explain Buhari’s speeches to arrive at the conversational implicatures generated in each of the given context within the studied texts. The study established the fact that Buhari’s utterances implied rather than stated what they meant and whatever a speaker implied could only be deciphered through the cooperative effort(s) of his listener(s). It was found that Buhari’s speeches had failed to address the needs and challenges of his followers; rather, the speeches were epitomes of tribal fanaticism and self-glorification. We also found out that his speeches are best understood when decoded pragmatically, using the theory of conversational implicature. The different maxims flouted in the speeches made them ambiguous and opaque to a non-critical reader and so the paper concludes that public office holders should always be unambiguous in their speech presentations as to address the immediate needs and challenges of their followers and that a language user should be very pragmatic in reading such political speeches so as to decode both the literal and implied meanings inherent in the speeches.